Psychoanalytic psychotherapy in Austria. Issue 2 (2nd April 2020) - Parth, Karoline; Fischer-Kern, Melitta; Rössler-Schülein, Hemma; Doering, Stephan
Abstract : With Vienna being the historical birthplace of psychoanalysis, the country is deeply connected to the discipline as a whole and holds a specific significance internationally. In Austria itself, psychoanalytic psychotherapies are currently embedded in a prospering and active training and research scene with several internationally connected societies. In order to contextualize the current state of the discipline and to describe the provisions offered by the national health care system for accessing psychoanalytic psychotherapies, this contribution first discusses the historical roots of psychoanalysis, its institutional beginnings as well as the profound difficulties and strains it underwent in the course of the Second World War and the takeover of the National Socialist regime. Furthermore, the resurrection of psychoanalysis in the post-war period as well as the process of institutionalization and academization that ensued will be discussed. Finally, an overview over current issues surrounding health care services, training requirements as well as future outlooks and challenges of psychoanalysis today is provided.